Arthrocladium, an unexpected human opportunist in Trichomeriaceae (Chaetothyriales). Issue 2 (February 2016) - Nascimento, Mariana M.F.; Selbmann, Laura; Sharifynia, Somayeh; Al-Hatmi, Abdullah M.S.; Voglmayr, Hermann; Vicente, Vania A.; Deng, Shuwen; Kargl, Alexandra; Moussa, Tarek A.A.; Al-Zahrani, Hassan S.; Almaghrabi, Omar A.; de Hoog, G. Sybren
Abstract: The family Trichomeriaceae ( Chaetothyriales ) mainly comprises epiphytic and epilithic organisms. In some species elaborate ascomata are formed, but for the great majority the species no asexual conidium formation is known other than simple fragmentation of the thallus. The present paper re-establishes the genus Arthrocladium with three non-sporulating species. One of these is described for a strain causing a fatal infection in a human patient with a rare genetic immune disorder.